Association between intoxication at last sexual intercourse and unprotected sex among men and women in Uganda - Bradley Townsend Kerridge; Delivette Castor; Phu Tran; Matthew Barnhart; Roger Pickering (Journal of Infection in Developing Countries)
Introduction: This study examined the association between intoxication at last sexual intercourse and unprotected sex using data derived from a nationally representative survey conducted in Uganda in 2011. Methodology: Multivariable logistic regression analyses were used to examine the intoxication-unprotected sex association separately among men and women, adjusted for sociodemographic and behavioral covariates that were also examined as moderators of the association. Results: Among men, intoxication at last sexual intercourse was almost entirely attributed to their own drinking, while women most frequently reported intoxication among their partners only. Among women, there was a significant association between their partner’s intoxication and unprotected sex (adjusted odds ratio (AOR) = 1.36; 95% confidence interval (CI) = 1.07-1.73. Intoxication was associated with unprotected sex among unmarried men (AOR = 2.09; 95%; CI = 1.45-2.84), an association not observed among married men. Conclusions: The results suggest that the alcohol-unprotected sex link should be incorporated within Ugandan National HIV Prevention Strategy. These interventions should be designed to target unmarried men. Programs that combine alcohol reduction and address structural factors that constrain women’s ability to negotiate condom use are also needed.